Enlarging the scale of knowledge in innovation networks: theoretical perspectives and policy issues - Riccardo Cappellin; Michael Steiner (European Regional Science Association (ERSA), 2002)
Nowadays, it is widely accepted that knowledge and learning are the core of competitiveness, international division of labour and agglomeration and exclusion phenomena. Yet we are still in need of a better understanding of the processes which allow access by individual regions both to codified knowledge and RTD networks as well as tacit knowledge and know-how at the international/interregional level. This paper will discuss possible approaches to analyze the mechanisms which operate at the international/interregional level and lead to higher forms of integration of industrial and service firms, not only in a commercial or financial perspective but also in knowledge and innovation networks. It will point to a need to develop policy strategies in support of institutions that create and transfer knowledge on a European scale and outline open questions for the creation of the necessary institutional background for the creation and the support of knowledge and innovation networks at this level and for the conditions of its transferability to Objective 1 regions and the EU candidate countries.
Keywords: 330